2019
DOI: 10.1021/acs.organomet.9b00211
|View full text |Cite
|
Sign up to set email alerts
|

Heteroleptic Heavier Alkaline Earth Metal Amide Complexes Stabilized by a Superbulky β-Diketiminate Ligand

Abstract: Heteroleptic alkaline earth metal (Ae = Ca, Sr, Ba) amide complexes with the superbulky β-diketiminate ligand DIPePBDI (CH­[C­(Me)­N-DIPeP]2, DIPeP = 2,6-di-iso-pentylphenyl) have been prepared by direct deprotonation of DIPePBDI-H with either AeN′′2 or AeN′′2·(THF)2 (N′′ = N­(SiMe3)2). Despite long reaction times of 5–14 days, this convenient one-step synthetic method has the major advantage that metal-pure products are obtained in generally quantitative yields. All (DIPePBDI)­AeN′′ and (DIPePBDI)­AeN′′·THF c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 44 publications
(117 reference statements)
1
43
0
Order By: Relevance
“…Although ( DIPP BDI)AeN′′ complexes may seem NMR‐pure, contamination with KN′′ can often not be noticed using NMR as an analytical method . We demonstrated that slight contamination with KN′′ leads to significantly lower stabilities and faster ligand exchange . This is likely due to the formation of intermediate ate complexes: ( DIPP BDI)AeN′′ + KN′′ → [( DIPP BDI)AeN′′ 2 – ] [K + ] .…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Although ( DIPP BDI)AeN′′ complexes may seem NMR‐pure, contamination with KN′′ can often not be noticed using NMR as an analytical method . We demonstrated that slight contamination with KN′′ leads to significantly lower stabilities and faster ligand exchange . This is likely due to the formation of intermediate ate complexes: ( DIPP BDI)AeN′′ + KN′′ → [( DIPP BDI)AeN′′ 2 – ] [K + ] .…”
Section: Resultsmentioning
confidence: 96%
“…The importance of the anagostic Ae··MeSi interaction, which is quantified by the discrepancy in the Ae-N-Si angles, decreases from Mg to Ba. Compared to the same series of ( DIPP BDI)AeN′′ complexes (Ae = Mg, [22] Ca, [23] Sr, [14] Ba [14] ), the Ae-N distances in the DPM complexes are consistently 0.01-0.08 Å longer. This fits with our earlier observations for DIPP DPM zinc complexes for which it could be shown that the DPM ligand is clearly weaker bound to the metal than the corresponding BDI ligand.…”
Section: Syntheses and Crystal Structuresmentioning
confidence: 93%
See 2 more Smart Citations
“…The synthesis of an heteroleptic boryloxide/aminoether‐phenolate [{LO NO4 }BaOB{CH(SiMe 3 ) 2 } 2 ], was successful, although this complex is not sufficiently stable in solution to be implemented in catalysis. Still, the choice of different ancillary ligands can of course be envisaged, for instance bulky β‐diketiminates or aminoether‐functionalised iminoanilides and amidinates . In line with other AE‐mediated reactions, it is possible that the resulting heteroleptic barium complexes will exhibit greater reaction rates than the homoleptic complexes used here.…”
Section: Resultsmentioning
confidence: 98%